2020
DOI: 10.3390/nano10091825
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Carbon, Silicon, and Metal-Based Nanoparticles to Sea Urchin Strongylocentrotus intermedius

Abstract: With the increasing annual production of nanoparticles (NPs), the risks of their harmful influence on the environment and human health are rising. However, our knowledge about the mechanisms of interaction between NPs and living organisms is limited. Prior studies have shown that echinoderms, and especially sea urchins, represent one of the most suitable models for risk assessment in environmental nanotoxicology. To the best of the authors’ knowledge, the sea urchin Strongylocentrotus intermedius has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 59 publications
0
16
0
2
Order By: Relevance
“…The embryos that reached correct development in 24 h were defined as normal. The features of normal development were described previously [34]. The number of normal embryos (Figure S2c), the embryos with developmental delays or impaired development (Figure S2d), and dead embryos were counted relative to the total number of zygotes.…”
Section: Sea Urchin Bioassaymentioning
confidence: 93%
See 2 more Smart Citations
“…The embryos that reached correct development in 24 h were defined as normal. The features of normal development were described previously [34]. The number of normal embryos (Figure S2c), the embryos with developmental delays or impaired development (Figure S2d), and dead embryos were counted relative to the total number of zygotes.…”
Section: Sea Urchin Bioassaymentioning
confidence: 93%
“…The protocol of the sea urchin bioassay has been described previously [34]. Adult individuals of the sea urchin S. intermedius were collected from Novi Dzhigit Bay (Peter the Great Bay, Sea of Japan, Russia).…”
Section: Sea Urchin Bioassaymentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Konstantin Pikula and co-workers demonstrated the use of sea urchin Strongylocentrotus intermedius as a novel approach to assess the nanotoxicity of NMs, such as Au NPs, silicon nanotubes (Si NTs), TiO 2 NPs, cadmium, and zinc sulfide (CdS and ZnS) nanocrystals. In summary, they observed the following trend in toxicity: Au NPs > Si NTs > CdS > ZnS > TiO 2 [94].…”
Section: Metallic-based Nanoparticlesmentioning
confidence: 93%
“…Our previous works addressed the question based on the responsible use of animals in biomedical research (the 3R principle) [ 13 ], focusing on a new methodology for in vitro/ex vivo nanostudies based on a nonmammalian model that is a proxy for humans, the sea urchin (marine invertebrate) [ 14 ]. Several studies have displayed the suitability of the sea urchin as a model for risk assessment in environmental nanotoxicology [ 15 , 16 ]. Our recent report on sea urchin immune cells exposed to AuNPs functionalized with polyvinylpyrrolidone (PVP–AuNPs, 1 and 10 μg mL −1 ) underlined the capability of particles to activate a transient innate immune response independently of the concentration used [ 5 ].…”
Section: Introductionmentioning
confidence: 99%